2016
DOI: 10.2967/jnumed.116.177048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation of a Dual Integrin αvβ3– and Gastrin-Releasing Peptide Receptor–Targeting PET Radiotracer, 68Ga-BBN-RGD

Abstract: This study aimed to document the first-in-human application of a 68 Ga-labeled heterodimeric peptide BBN-RGD (bombesin-RGD) that targets both integrin a v b 3 and gastrin-releasing peptide receptor (GRPR). We evaluated the safety and assessed the clinical diagnostic value of 68 Ga-BBN-RGD PET/CT in prostate cancer patients in comparison with 68 Ga-BBN. Methods: Five healthy volunteers (4 men and 1 woman; age range, 28-53 y) were enrolled to validate the safety of 68 Ga-BBN-RGD. Dosimetry was calculated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…In particular, they can be targeted by bombesin (i.e., a 14-AA peptide with the sequence pEQRLGNQWAVGHLM-NH 2 ) or arginine-glycine-aspartic acid (RGD) derivatives. 79,80 Consequently, in 2008, van Lier and co-workers were the first to synthesize a bombesin-Pc conjugate to target the GRP receptor. 54 To this end, they made use of tetrasulphonated Al(III)Pc (AlPcS 4 ), observing that the photodynamic efficacy in PC-3 human prostate cancer cells had improved with conjugation.…”
Section: 22mentioning
confidence: 99%
“…In particular, they can be targeted by bombesin (i.e., a 14-AA peptide with the sequence pEQRLGNQWAVGHLM-NH 2 ) or arginine-glycine-aspartic acid (RGD) derivatives. 79,80 Consequently, in 2008, van Lier and co-workers were the first to synthesize a bombesin-Pc conjugate to target the GRP receptor. 54 To this end, they made use of tetrasulphonated Al(III)Pc (AlPcS 4 ), observing that the photodynamic efficacy in PC-3 human prostate cancer cells had improved with conjugation.…”
Section: 22mentioning
confidence: 99%
“…2 and Table 1). This fact could be explained based on the concentration of unlabeled peptides Affinity, cell uptake, and viability assays indicated that 177 Lu-iPSMA-RGD was not able to concomitantly recognize two receptors on the cell surface or to improve the cell uptake concerning 177 Lu-iPSMA or 177 Lu-RGD monomers, as other authors have reported for heterobivalent molecules [11][12][13]. However, the intrinsic heterogenicity of human tumors, as well as changes in phenotype during disease progression, including the different level expression of cell surface receptors, is well-known.…”
Section: In Vitro Evaluation and Cell Studiesmentioning
confidence: 91%
“…The research on new heterobivalent radiopharmaceuticals that interact with two different targets on tumor cells is a strategy for the enhancement of tumor imaging and therapy [11][12][13]. Therefore, a heterobivalent conjugate of iPSMA and RGD is expected to improve the recognition of cancer cells positive for PSMA and a(v)b (3) integrins.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, GRP and α v β 3 integrin are proteins that are expressed in different tumours, being a receptor of a peptide called bombesin in the first case, and of a peptide called RGD triad or arginylglycylaspartic acid in the second case. [17,25] Van Lier et al have developed different Zn(II) Pc-bombesin and Zn(II)Pc-RGD conjugates. [26] These bioconjugates were evaluated in cell lines that express GRP and integrin receptors and the results showed that the first one, a Zn(II)Pc-bombes in biohybrid, expressed a good aqueous solubility and was a potential candidate for being used as fluorescence imaging probe and photodynamic agent.…”
Section: Phthalocyaninesmentioning
confidence: 99%